Sức nén thông tin trong câu văn Nguyễn Huy Thiệp - Trương, Thị Minh Phương (Trường Đại học Đà Lạt, 2012)
Nguyen Huy Thiep is a short story writer with an "Original" personality. His writings, though compact, possesses the intense impact of novel, dealing with vital life issues of the lonely, the eccentric, the handicapped - particularly the decadent, 'ingrate', 'boring' figures in modem life.